Potensi Bacillus sp. Sebagai Agen Antagonis Terhadap Athelia rolfsii Penyebab Busuk Pangkal Batang Kedelai (Glycine max L.) - Cahya, Khotima Dwi; Kawuri, Retno; Wijana, I Made Sara (Metamorfosa: Journal of Biological Sciences, 2022)
Athelia rolfsii can cause stem rot on soybean plants with symptoms of infection at the base of the stem bordering the soil surface that caused reduce soybean yields up to 75%. Disease control with chemical fertilizers have negative impact on the environment.  Bacillus  sp. as antagonistic agent thats known produced enzymes, antibiotics, and siderophore capable to suppressed pathogenic fungus growth. This study aims to determine the potential of isolates  Bacillus  sp. which was isolated from the groundnut rhizosphere to inhibit  A. rolfsii  in vitro and to determine concentration of culture Bacillus  sp. to suppress the growth of  A. rolfsii  in green house.  The research used a completely randomized design (RAL), where the treatment was derived from the concentration volume of culture Bacillus sp. which shows the best resistance zone. Parameter observed in this research were the inhibition zone, disease incidence, and disease severity. Data were analyzed used analysis of variance (ANOVA). The results obtained 6 isolates of Bacillus sp. Isolate Bacillus sp.1 as isolate with the best percentage of inhibition in suppressing the growth of A. rolfsii  (79,44%) then tested on greenhouse. Culture Bacillus sp.1 (10 mL) with a density 1x10 8 cells/mL was able to suppress incidene of stem rot disease up to 53,38 ± 18,23% and the percentage of disease severity 67,78 ± 19,40% during 7 HST. Amistar top as positive control can supress percentage incidence and disease severity up to 86,68 ± 18,25%. Culture of Bacillus sp.1 can be used as an antagonizing agent in stem rot disease caused by A. rolfsii . Keyword : Antagonist, Athelia rolfsii , Bacillus sp., Soybean